New Observations of Solar Wind 1/f Turbulence Spectrum from Parker Solar Probe - Huang, Zesen; Sioulas, Nikos; Shi, Chen; Velli, Marco; Bowen, Trevor; Davis, Nooshin; Chandran, B. D. G.; Matteini, Lorenzo; Kang, Ning; Shi, Xiaofei; Huang, Jia; Bale, Stuart D.; et al. (Astrophysical journal. Letters, 2023)
The trace magnetic power spectrum in the solar wind is known to be characterized by a double power law at scales much larger than the proton gyro-radius, with flatter spectral exponents close to −1 found at the lower frequencies below an inertial range with indices closer to [−1.5, −1.67]. The origin of the 1/ f range is still under debate. In this study, we selected 109 magnetically incompressible solar wind intervals ( δ ∣ B ∣/∣ B ∣ ≪ 1) from Parker Solar Probe encounters 1–13 that display such double power laws, with the aim of understanding the statistics and radial evolution of the low-frequency power spectral exponents from Alfvén point up to 0.3 au. New observations from closer to the Sun show that in the low-frequency range solar wind, turbulence can display spectra much shallower than 1/ f , evolving asymptotically to 1/ f as advection time increases, indicating a dynamic origin for the 1/ f range formation. We discuss the implications of this result on the Matteini et al. conjecture for the 1/ f origin as well as example spectra displaying a triple power law consistent with the model proposed by Chandran et al., supporting the dynamic role of parametric decay in the young solar wind. Our results provide new constraints on the origin of the 1/ f spectrum and further show the possibility of the coexistence of multiple formation mechanisms.